Preparation method of iron phosphate for high-compaction lithium iron phosphate

By using glucose as an additive in the preparation process of iron phosphate dihydrate, the problem of primary particles agglomeration of iron phosphate dihydrate is solved, and the physical and chemical indicators and electrical properties of anhydrous iron phosphate are significantly improved.

CN119706771APending Publication Date: 2025-03-28ZHEJIANG YOUSHAN NEW ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411932707.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, primary particles of iron phosphate dihydrate are severely agglomerated, resulting in the melting bulk weight problem of anhydrous ferric phosphate and affecting the performance of electrical properties.

Method used

Using glucose as an additive, by controlling the growth morphology of grains, uniformly dispersed iron phosphate dihydrate is prepared to reduce the agglomeration of primary particles. The specific steps include preparing a phosphoric acid solution, hydrogen peroxide solution, iron salt solution and phosphoric salt solution, adding a glucose solution and reacting under stirring conditions, then filtering, washing, and drying, and finally obtaining anhydrous iron phosphate through calcination treatment.

Benefits of technology

The agglomeration of primary particles of iron phosphate dihydrate is significantly reduced, the burn resistance of iron phosphate and the iron content of anhydrous iron phosphate are improved, forming a dense and uniform structure, and improving electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706771A_ABST
    Figure CN119706771A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of iron phosphate for high-compaction lithium iron phosphate, and relates to the technical field of lithium ion battery materials, the preparation method comprises the following steps: S1, preparing a phosphoric acid solution, a hydrogen peroxide solution, an iron salt solution, a phosphorus salt solution and a glucose solution; s2, bottoming with a glucose solution, heating, and adding a hydrogen peroxide solution, an iron salt solution and a phosphorus salt solution to obtain basic ammonium ferric phosphate slurry; s3, reacting for 10 to 60 minutes to obtain yellow slurry A; s4, filtering and washing to obtain a yellow filter cake; s5, adding pure water to obtain yellow slurry B; s6, adding a phosphoric acid solution, heating and preserving heat to obtain white slurry C; s7, filtering, washing and drying to obtain iron phosphate dihydrate with a large and small particle compound structure; s8, calcining to obtain anhydrous iron phosphate; glucose is used as an additive, so that the growth morphology of iron phosphate dihydrate crystal grains is effectively controlled, and the agglomeration phenomenon of primary particles of iron phosphate dihydrate is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to a method for preparing high iron-phosphorus ratio iron phosphate. Background Art

[0002] With the rapid development of new energy industry, electric vehicles and smart Internet of Things, the market demand for lithium-ion batteries has grown rapidly. According to the different positive electrode materials, lithium-ion batteries are divided into lithium cobalt oxide, lithium manganese oxide, ternary material system and lithium iron phosphate. Among them, lithium iron phosphate batteries have become the most promising lithium-ion batteries due to their excellent cycle performance and low preparation cost.

[0003] The patent document with publication number CN117865095A mixes a wet-process phosphoric acid solution with an aluminum shielding agent into a mixed solution, adds a pH adjuster and then allows the mixture to stand, the aluminum shielding agent is at least one of malonate, succinate and phthalate, and then the mixed solution is water-bathed under stirring, and ferric sulfate and dihydrate ferric phosphate seeds are added to the mixed solution. After the reaction, the solid-liquid separation obtains a solid, and after washing, dihydrate ferric phosphate is obtained, wherein the primary particles are flaky and tightly stacked, and the secondary particles are agglomerated into a spherical shape.

[0004] However, the patent does not solve the problem of agglomeration of primary particles of dihydrate iron phosphate. The agglomeration of primary particles of dihydrate morphology will lead to the problem of sintering density of anhydrous iron phosphate. After being prepared into lithium iron phosphate, large particles will be produced. Although compaction will be improved, it will affect the electrical performance. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing uniformly dispersed ferric phosphate dihydrate, wherein glucose is used as an additive to control the grain growth morphology and solve the problem of serious agglomeration of primary particles of ferric phosphate dihydrate, which is specifically as follows: A method for preparing uniformly dispersed ferric phosphate dihydrate, comprising the following steps: S1. Prepare 60-85wt% phosphoric acid solution, 10-25wt% hydrogen peroxide solution, iron salt solution, phosphate salt solution and glucose solution respectively; the concentration of the glucose solution is 0.05-0.5 mol / L; S2, using glucose solution as the base, heating the glucose solution to 30-80°C under continuous stirring, adding hydrogen peroxide solution, iron salt solution and phosphate salt solution to obtain basic ammonium ferric phosphate slurry; the pH value of the basic ammonium ferric phosphate slurry is 2.0-3.5; S3. Under continuous stirring, the basic ammonium ferric phosphate slurry is reacted for 10-60 minutes to obtain a yellow slurry A; S4, filtering and washing the yellow slurry A to obtain a yellow filter cake; S5, adding pure water to the yellow filter cake to obtain yellow slurry B; S6. Add the phosphoric acid solution prepared in step S1 to the yellow slurry B under continuous stirring, raise the temperature to 80-100° C., and keep the temperature for 60-120 min after the slurry changes to white, to obtain white slurry C; S7, filtering, washing and drying the white slurry C to obtain ferric phosphate dihydrate having a composite structure of large and small particles; S8. After calcining the dihydrate ferric phosphate, anhydrous ferric phosphate with a composite structure of large and small particles is obtained.

[0006] Moreover, in step S1, the concentration of phosphorus in the phosphate solution is 0.5-1.5 mol / L; the phosphate solution is prepared from any one of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.

[0007] Moreover, in step S1, the phosphate salt solution is prepared from phosphoric acid, and ammonia water, liquid alkali and sulfuric acid solution are added to adjust the pH of the phosphate salt solution to 4-8; when the pH is less than 4, liquid alkali or ammonia solution is added; when the pH is greater than 8.0, sulfuric acid solution is added.

[0008] Moreover, in step S1, the concentration of the iron element in the ferrous salt solution is 0.5-1.5 mol / L.

[0009] Moreover, in step S1, the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder, and iron sheet; and the glucose solution is prepared from glucose raw material.

[0010] Moreover, in step S2, the molar ratio of iron element to phosphorus element in the iron salt solution and the phosphate salt solution is 1:0.9-1:1.2; the concentration of the hydrogen peroxide solution is 10%-25%; and the molar ratio of iron element to hydrogen peroxide in the iron salt solution is 1:0.5-1:0.7.

[0011] Moreover, in step S2, the pH value of the basic ammonium ferric phosphate slurry is controlled by sulfuric acid solution, liquid alkali or ammonia solution; when the pH is greater than 3.5, sulfuric acid solution is added; when the pH is less than 2.0, liquid alkali or ammonia solution is added.

[0012] Moreover, in step S2, the specific method of adding the hydrogen peroxide solution, the iron salt solution and the phosphate salt solution is to mix the hydrogen peroxide solution with the phosphate salt solution, and then add the hydrogen peroxide solution and the iron salt solution to the glucose solution within 30 minutes.

[0013] Moreover, in step S6, the molar ratio of phosphorus in the phosphoric acid solution to iron in the yellow slurry A is n(P):n(Fe)=0.1-0.5:1.

[0014] Moreover, in step S8, the primary particles of the anhydrous ferric phosphate are granular, and the size of the primary particles is 10-50 nm.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a method for preparing uniformly dispersed ferric phosphate dihydrate. The preparation method uses glucose as an additive, effectively controls the growth morphology of ferric phosphate dihydrate grains, significantly reduces the agglomeration of primary particles of ferric phosphate dihydrate, solves the problem of poor electrical properties of the iron-lithium end caused by the agglomeration of primary particles of ferric phosphate dihydrate, and can adjust the morphology of ferric phosphate dihydrate and the physical and chemical indicators of anhydrous ferric phosphate. Glucose has a certain reducing property and can reduce oxidized trivalent iron to divalent iron during the synthesis reaction. The divalent iron reacts with phosphate to generate ferrous phosphate and also reacts with hydrogen peroxide to generate. With the addition of hydrogen peroxide, the synthesis system changes from a mixture of divalent iron and trivalent iron to basic ammonium ferric phosphate.

[0016] 2. Since the primary particles of dihydrate iron phosphate prepared by the present invention are evenly dispersed, the burning resistance of iron phosphate and the iron content of anhydrous iron phosphate can be improved, and the primary particle size is moderate (10-50 nm), which helps to form a more dense and uniform structure in the subsequent preparation of lithium iron phosphate.

[0017] 3. The ferric phosphate dihydrate and anhydrous ferric phosphate prepared by the present invention both have a structure of composite large and small particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Example 1; Figure 2 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Example 2; Figure 3 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Example 3; Figure 4 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Comparative Example 1; Figure 5 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Comparative Example 2; Figure 6 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Comparative Example 3; Figure 7 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Comparative Example 4 are shown; Figure 8 These are SEM images of dihydrate iron phosphate and anhydrous iron phosphate prepared in Comparative Example 5. DETAILED DESCRIPTION

[0019] Example 1 A method for preparing uniformly dispersed ferric phosphate dihydrate comprises the following steps: S1, prepare 60wt% phosphoric acid solution, 10wt% hydrogen peroxide solution, iron salt solution, phosphate salt solution, and glucose solution respectively; the concentration of the glucose solution is 0.05wt%; S2, using glucose solution as the base, heating the glucose solution to 30° C. under continuous stirring, adding hydrogen peroxide solution, iron salt solution, and phosphate salt solution to obtain basic ammonium ferric phosphate slurry; the pH value of the basic ammonium ferric phosphate slurry is 2.0; S3. Under continuous stirring, the basic ammonium ferric phosphate slurry was reacted for 10 minutes to obtain a yellow slurry A; S4, filtering and washing the yellow slurry A to obtain a yellow filter cake; S5, adding pure water to the yellow filter cake to obtain yellow slurry B; S6. Add the phosphoric acid solution prepared in step S1 to the yellow slurry B under continuous stirring, raise the temperature to 80-100° C., and keep the temperature for 60 min after the slurry changes to white, to obtain white slurry C; S7, filtering, washing and drying the white slurry C to obtain ferric phosphate dihydrate having a composite structure of large and small particles; S8. After calcining the dihydrate ferric phosphate, anhydrous ferric phosphate with a composite structure of large and small particles is obtained.

[0020] Furthermore, in step S1, the concentration of phosphorus in the phosphate solution is 0.5 mol / L; and the phosphate solution is prepared from ammonium monohydrogen phosphate.

[0021] Furthermore, in step S1, the phosphate salt solution is prepared from phosphoric acid, and liquid alkali and sulfuric acid solution are added to adjust the pH of the phosphate salt solution to 4.

[0022] Furthermore, in step S1, the concentration of iron in the ferrous salt solution is 0.5 mol / L.

[0023] Furthermore, in step S1, the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder, and iron sheet; and the glucose solution is prepared from glucose raw material.

[0024] Furthermore, in step S2, the molar ratio of iron element to phosphorus element in the iron salt solution and the phosphorus salt solution is 1:0.9; the concentration of the hydrogen peroxide solution is 10%; and the molar ratio of iron element to hydrogen peroxide in the iron salt solution is 1:0.5.

[0025] Furthermore, in step S2, the pH value of the basic ammonium ferric phosphate slurry is controlled by a sulfuric acid solution and an ammonia solution.

[0026] Furthermore, in step S2, the specific method of adding the hydrogen peroxide solution, the iron salt solution, and the phosphate salt solution is to mix the hydrogen peroxide solution with the phosphate salt solution, and then add the hydrogen peroxide solution and the iron salt solution to the glucose solution within 30 minutes.

[0027] Furthermore, in step S6, the molar ratio of the phosphorus element in the phosphoric acid solution to the iron element in the yellow slurry A is n(P):n(Fe)=0.1:1.

[0028] Furthermore, in step S8, the primary particles of the anhydrous ferric phosphate are granular, and the size of the primary particles is 10-50 nm.

[0029] Example 2 A method for preparing uniformly dispersed ferric phosphate dihydrate comprises the following steps: S1. Prepare 85wt% phosphoric acid solution, 25wt% hydrogen peroxide solution, iron salt solution, phosphate salt solution and glucose solution respectively; the concentration of the glucose solution is 0.2 mol / L; S2, using glucose solution as the base, heating the glucose solution to 80° C. under continuous stirring, adding hydrogen peroxide solution, iron salt solution, and phosphate salt solution to obtain basic ammonium ferric phosphate slurry; the pH value of the basic ammonium ferric phosphate slurry is 3.5; S3. Under continuous stirring, the basic ammonium ferric phosphate slurry was reacted for 60 minutes to obtain a yellow slurry A; S4, filtering and washing the yellow slurry A to obtain a yellow filter cake; S5, adding pure water to the yellow filter cake to obtain yellow slurry B; S6. Add the phosphoric acid solution prepared in step S1 to the yellow slurry B under continuous stirring, raise the temperature to 100° C., and keep the temperature for 120 min after the slurry changes to white, to obtain a white slurry C; S7, filtering, washing and drying the white slurry C to obtain ferric phosphate dihydrate having a composite structure of large and small particles; S8. After calcining the dihydrate ferric phosphate, anhydrous ferric phosphate with a composite structure of large and small particles is obtained.

[0030] Furthermore, in step S1, the concentration of phosphorus in the phosphate solution is 1.5 mol / L; and the phosphate solution is derived from sodium monohydrogen phosphate.

[0031] Furthermore, in step S1, the phosphate salt solution is prepared from phosphoric acid, and liquid alkali and sulfuric acid solution are added to adjust the pH of the phosphate salt solution to 8.

[0032] Furthermore, in step S1, the concentration of iron in the ferrous salt solution is 1.5 mol / L.

[0033] Furthermore, in step S1, the ferrous salt solution is prepared from ferrous chloride; and the glucose solution is prepared from glucose raw material.

[0034] Furthermore, in step S2, the molar ratio of iron element to phosphorus element in the iron salt solution and the phosphorus salt solution is 1:1.2; the concentration of the hydrogen peroxide solution is 25%; and the molar ratio of iron element to hydrogen peroxide in the iron salt solution is 1:0.7.

[0035] Furthermore, in step S2, the pH value of the basic ammonium ferric phosphate slurry is controlled by a sulfuric acid solution and an ammonia solution.

[0036] Furthermore, in step S2, the specific method of adding the hydrogen peroxide solution, the iron salt solution, and the phosphate salt solution is to mix the hydrogen peroxide solution with the phosphate salt solution, and then add the hydrogen peroxide solution and the iron salt solution to the glucose solution within 30 minutes.

[0037] Furthermore, in step S6, the molar ratio of the phosphorus element in the phosphoric acid solution to the iron element in the yellow slurry A is n(P):n(Fe)=0.5:1.

[0038] Furthermore, in step S8, the primary particles of the anhydrous ferric phosphate are granular, and the size of the primary particles is 10-50 nm.

[0039] Example 3 A method for preparing uniformly dispersed ferric phosphate dihydrate comprises the following steps: S1. Prepare 70wt% phosphoric acid solution, 18wt% hydrogen peroxide solution, iron salt solution, phosphate salt solution and glucose solution respectively; the concentration of the glucose solution is 0.25mol / L; S2, using glucose solution as the base, heating the glucose solution to 45° C. under continuous stirring, adding hydrogen peroxide solution, iron salt solution, and phosphate salt solution to obtain basic ammonium ferric phosphate slurry; the pH of the basic ammonium ferric phosphate slurry is 3; S3. Under continuous stirring, the basic ammonium ferric phosphate slurry was reacted for 35 minutes to obtain a yellow slurry A; S4, filtering and washing the yellow slurry A to obtain a yellow filter cake; S5, adding pure water to the yellow filter cake to obtain yellow slurry B; S6. Add the phosphoric acid solution prepared in step S1 to the yellow slurry B under continuous stirring, raise the temperature to 80-100° C., and keep the temperature for 90 min after the slurry changes to white, to obtain white slurry C; S7, filtering, washing and drying the white slurry C to obtain ferric phosphate dihydrate having a composite structure of large and small particles; S8. After calcining the dihydrate ferric phosphate, anhydrous ferric phosphate with a composite structure of large and small particles is obtained.

[0040] Furthermore, in step S1, the concentration of phosphorus in the phosphate salt solution is 1.4 mol / L; and the phosphate salt solution is prepared from sodium dihydrogen phosphate.

[0041] Furthermore, in step S1, the phosphate salt solution is prepared from phosphoric acid, and ammonia water and sulfuric acid solution are added to adjust the pH of the phosphate salt solution to 4-8.

[0042] Furthermore, in step S1, the concentration of iron in the ferrous salt solution is 1.4 mol / L.

[0043] Furthermore, in step S1, the ferrous salt solution is prepared from ferrous sulfate; and the glucose solution is prepared from glucose raw material.

[0044] Furthermore, in step S2, the molar ratio of iron element to phosphorus element in the iron salt solution and the phosphorus salt solution is 1:1.03; the concentration of the hydrogen peroxide solution is 15%; and the molar ratio of iron element to hydrogen peroxide in the iron salt solution is 1:0.6.

[0045] Furthermore, in step S2, the pH value of the basic ammonium ferric phosphate slurry is controlled by sulfuric acid solution, liquid alkali or ammonia solution.

[0046] Furthermore, in step S2, the specific method of adding the hydrogen peroxide solution, the iron salt solution, and the phosphate salt solution is to mix the hydrogen peroxide solution with the phosphate salt solution, and then add the hydrogen peroxide solution and the iron salt solution to the glucose solution within 30 minutes.

[0047] Furthermore, in step S6, the molar ratio of the phosphorus element in the phosphoric acid solution to the iron element in the yellow slurry A is n(P):n(Fe)=0.4:1.

[0048] Furthermore, in step S8, the primary particles of the anhydrous ferric phosphate are granular, and the size of the primary particles is 10-50 nm.

[0049] Comparative Example 1 The difference between this comparative example and Example 3 is that the glucose solution in step S2 is replaced with iron salt as the base, and the base solution is heated to 45° C.; a phosphate solution and a hydrogen peroxide mixture are added to the base solution to obtain basic ammonium ferric phosphate slurry.

[0050] Comparative Example 2 The difference between this comparative example and Example 3 is that the glucose solution in step S2 is replaced with iron salt as the base, the base liquid is heated to 45°C, and a phosphate solution and a hydrogen peroxide mixture are added to the base liquid to obtain basic ammonium ferric phosphate slurry; in step S5, the yellow filter cake is added with pure water and glucose solution to obtain yellow slurry B.

[0051] Comparative Example 3 The difference between this comparative example and Example 3 is that the glucose solution in step 2 is replaced with pure water as the base, and the base solution is heated to 45°C.

[0052] Comparative Example 4 The difference between this comparative example and Example 3 is that the concentration of the glucose solution is 0.04 mol / L.

[0053] Comparative Example 5 The difference between this comparative example and Example 3 is that the concentration of the glucose solution is 0.6 mol / L.

[0054] Experimental Section

[0055] Experiment 1 The dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Examples 1, 2, 3 and Comparative Examples 1-5 were respectively subjected to electron microscope scanning. The results show that Figure 1-7 , Figure 1 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Example 1; Figure 2 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Example 2; Figure 3 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Example 3; Figure 4 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Comparative Example 1; Figure 5 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Comparative Example 2; Figure 6 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Comparative Example 3; Figure 7 The SEM images of the dihydrated ferric phosphate and anhydrous ferric phosphate prepared in Comparative Example 4 are shown; Figure 8 These are SEM images of dihydrate iron phosphate and anhydrous iron phosphate prepared in Comparative Example 5.

[0056] from Figure 1 , 2 As can be seen from Examples 1, 2 and 3, the ferric phosphate dihydrate prepared in Examples 1, 2 and 3 has a certain degree of dispersion and a structure of a composite of large and small particles. The anhydrous ferric phosphate "inherits" this feature and also has a structure of a composite of large and small particles.

[0057] from Figure 4It can be seen that, since no glucose is added to Comparative Example 1, the primary particles of the dihydrate morphology are in the form of small flakes, the primary particles are tightly packed, and the anhydrous morphology has a partial fusion phenomenon.

[0058] from Figure 5 It can be seen that in Comparative Example 2, the position of glucose addition was changed. When glucose did not participate in the synthesis reaction, it did not play a role in dispersing the primary particles of dihydrate ferric phosphate. The primary particles were tightly packed, and the anhydrous ferric phosphate morphology had a local fusion phenomenon.

[0059] from Figure 6 It can be seen that the primary particles of ferric phosphate dihydrate prepared in Comparative Example 3 are significantly smaller than those in Experiment 1, and the primary particles are severely agglomerated and not as dispersed as the primary particles in Experiment 1. Therefore, the anhydrous ferric phosphate after calcination is severely fused. The reason may be that in Comparative Example 3, pure water is used as the base. On the one hand, the raw material concentration is reduced when iron salt and phosphate salt are added together. On the other hand, the pH value of the system is increased, which changes the nucleation rate and the crystal nucleus growth rate, and increases the degree of agglomeration between the primary particles.

[0060] from Figure 7 It can be seen that Comparative Example 4 is a low-concentration glucose solution, and the primary particles of ferric phosphate dihydrate prepared are slightly smaller than those of Example 1, but the primary particles are slightly dispersed.

[0061] from Figure 8 It can be seen that in Comparative Example 5, which is a high-concentration glucose solution, the primary particles of the prepared ferric phosphate dihydrate are larger than those in the example, and the degree of dispersion of the primary particles is much greater than that in the example.

[0062] Experiment 2 The physical and chemical properties of the anhydrous ferric phosphate prepared in Examples 2-3 and Comparative Examples 1-5 were measured, and the results are shown in Table 1 below.

[0063] Table 1 Physical and chemical data results of iron phosphate

[0064] Comparative Examples 1 and 2 of the present invention are a method for preparing iron phosphate of conventional morphology. The ratio and reaction conditions of Comparative Example 1 are the same as those of Example 3. The difference from Example 3 is that the base liquid is different. Comparative Example 2 adds glucose solution on the basis of Comparative Example 1. From the data of anhydrous iron phosphate, the difference is not much, because glucose does not participate in the synthesis reaction. The primary particles of dihydrate iron phosphate tend to be arranged in order to form flaky secondary particles. The flaky particles are then staggered at a certain angle to assemble into spherical particles. The particle size distribution of iron phosphate of this structure is too narrow, and there are many pores between the particles, making it difficult to obtain a higher compaction density. In Comparative Example 3 of the present invention, from the perspective of the ratio of anhydrous iron phosphate, the ratio of Comparative Example 3 is much lower than that of the embodiment, and the ratio is small. It is easy to burn into large particles when preparing lithium iron phosphate, which seriously affects the electrical properties. The physical and chemical data of anhydrous iron phosphate in Comparative Example 4 are relatively ideal, but the dispersion degree of the primary example of dihydrate iron phosphate is low. Although the dispersion effect is very significant in Comparative Example 5, the physical and chemical indicators of anhydrous iron phosphate are abnormal, and it is difficult to obtain a higher compaction density and electrical properties.

Claims

1. A method for preparing iron phosphate for high-density lithium iron phosphate, characterized in that: The following steps are involved: S1, respectively prepare 60-85wt% phosphoric acid solution, 10-25wt% hydrogen peroxide solution, iron salt solution, phosphate solution, and glucose solution; The concentration of the glucose solution is 0.05-0.5 mol / L; S2, using glucose solution as the base, heating the glucose solution to 30-80°C under continuous stirring, adding hydrogen peroxide solution, iron salt solution and phosphate salt solution to obtain basic ammonium ferric phosphate slurry; the pH value of the basic ammonium ferric phosphate slurry is 2.0-3.5; S3. Under continuous stirring, the basic ammonium ferric phosphate slurry is reacted for 10-60 minutes to obtain a yellow slurry A; S4, filtering and washing the yellow slurry A to obtain a yellow filter cake; S5, adding pure water to the yellow filter cake to obtain yellow slurry B; S6. Add the phosphoric acid solution prepared in step S1 to the yellow slurry B under continuous stirring, raise the temperature to 80-100° C., and keep the temperature for 60-120 min after the slurry changes to white, to obtain white slurry C; S7, filtering, washing and drying the white slurry C to obtain ferric phosphate dihydrate having a composite structure of large and small particles; S8. After calcining the dihydrate ferric phosphate, anhydrous ferric phosphate with a composite structure of large and small particles is obtained.

2. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 1, characterized in that: In step S1, the concentration of phosphorus in the phosphate solution is 0.5-1.5 mol / L; the phosphate solution is prepared from any one of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate.

3. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 1, characterized in that: In step S1, the phosphate salt solution is prepared from phosphoric acid, and ammonia water, liquid alkali and sulfuric acid solution are added to adjust the pH of the phosphate salt solution to 4-8.

4. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 1, characterized in that: In step S1, the concentration of iron in the ferrous salt solution is 0.5-1.5 mol / L.

5. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 4, characterized in that: In step S1, the ferrous salt solution is prepared from ferrous sulfate, ferrous nitrate, ferrous chloride, iron powder and iron sheet; and the glucose solution is prepared from glucose raw material.

6. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 1, characterized in that: In step S2, the molar ratio of iron to phosphorus in the iron salt solution and the phosphorus salt solution is 1:0.9-1:1.2; the concentration of the hydrogen peroxide solution is 10%-25%; and the molar ratio of iron to hydrogen peroxide in the iron salt solution is 1:0.5-1:0.

7.

7. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 1, characterized in that: In step S2, the pH value of the basic ammonium ferric phosphate slurry is controlled by sulfuric acid solution, liquid alkali or ammonia solution.

8. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 1, characterized in that: In step S2, the specific method of adding the hydrogen peroxide solution, the iron salt solution and the phosphate salt solution is to mix the hydrogen peroxide solution with the phosphate salt solution, and then add the hydrogen peroxide solution and the iron salt solution to the glucose solution within 10-60 minutes.

9. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 1, characterized in that: In step S6, the molar ratio of phosphorus in the phosphoric acid solution to iron in the yellow slurry A is n(P):n(Fe)=0.1-0.5:

1.

10. The method for preparing an iron phosphate material for high-density lithium iron phosphate according to claim 1, characterized in that: In step S8, the primary particles of the anhydrous ferric phosphate are granular, and the size of the primary particles is 10-50 nm.

Citation Information

Patent Citations

  • Method for preparing iron phosphate dihydrate from wet-process phosphoric acid

    CN117865095A